An acute febrile outbreak in a refugee community of an Italian asylum seeker center: lessons learned. (October 2018) - Ciccozzi, M.; Riva, E.; Vita, S.; Cella, E.; Fogolari, M.; Spoto, S.; Lopalco, M.; Ceccarelli, G.; Angeletti, S.
Abstract: Objectives: The management of infectious outbreaks in closed settings represents an important public health issue. An outbreak of acute febrile syndrome affecting 22 refugees resident at the Asylum Seekers Centre of Castelnuovo di Porto in Rome has been reported, and the preventive and control measures adopted have been described as an example of public health safety. Methods: Pharyngeal swab and whole-blood samples were collected from 22 cases observed and analyzed for standard bacterial cultures and respiratory and herpesviruses by qualitative CLART PneumoVir2 and Entherpex microarray. Results: A possible respiratory-transmitted etiology and a concomitant reactivation of multiple herpesviruses have been evidenced. The epidemiological investigation showed that the spread of the epidemic was promoted because patients were hosted in neighboring rooms or in the same room, facilitating the rapid spread of infectious disease. Conclusions: The potential way of transmission was supposed, and preventive measures for infection control were adopted. The measures adopted are an example of best practice for outbreak management, and the microbiological surveillance is recommended for public health improvement. Highlights: Outbreak of acute febrile syndrome affecting refugees resident at an Italian Asylum Seeker Center. Respiratory-transmitted etiology and a concomitant reactivation of multiple herpesviruses. Spread of epidemic promoted by patients hosted in neighboring rooms or in the same room. Preventive measures for infection control adopted to limit the outbreak. Example of best practice for outbreak management.